Effect of (α + β) heat treatment on microstructure and mechanical properties of (TiB + TiC)/Ti–B20 matrix composite. (15th December 2015) - Rahoma, H.K.S.; Wang, X.P.; Kong, F.T.; Chen, Y.Y.; Han, J.C.; Derradji, Mehdi
Abstract: For the first stage, a metastable β titanium alloy, Ti–3.5Al–5Mo–4V–2Cr–2Sn–2Zr–1Fe reinforced with trace amounts of TiB whiskers and TiC particles was fabricated by vacuum arc melting process and hot forging followed by heat treatment at 780 °C/740 °C, then by aging at 500 °C, 550 °C, 570 °C and 600 °C. For the second stage, the unreinforced titanium alloy was also fabricated by the same process. The microstructural characteristics were investigated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Traces of TiB whiskers and TiC particles (2.2 vol.%) with a volume ratio of 2:3 synthesized in situ exerted a hybrid reinforcing effect on the β titanium alloy. The reinforcements were uniformly distributed in the matrix and the elastic modulus was improved about 25 GPa. Ultimate tensile strength and yield strength achieves about 1625 MPa and 1500MPa respectively, with ductility at 7% when the aging temperature is 500 °C. The ductility of (TiB + TiC)/(Ti–3.5Al–5Mo–4 V–2Cr–2Sn–2Zr–1Fe) matrix composite could be enhanced by increasing the aging temperatures. After 780 °C followed by aging at 570 °C, excellent strength and plasticity properties were obtained (ultimate tensile strength of matrix alloy is 1350 MPa with elongation of 18% and ultimate tensile strength of composite is 1500 MPa with elongation of 13%). Graphical abstract: Highlights: The hybrid of TiBw and TiCp improves Young's modulus of Ti–B20 alloy to 120 ± 5 GPa. 2.2 vol.% (TiB–TiC)/B20 alloys have a rapid aging response. The composite obtained a high strength over 1600 MPa, with its ductility at about 7%.